Implementasi Model Pembelajaran Problem Based Learning (PBL) dalam Meningkatkan Minat dan Fokus Siswa pada Mata Pelajaran Pendidikan Agama Islam di Sekolah Menengah Kejuruan - Mardia Hayati; Andhika Geovanie Putra; Irsyad Zamli Pratama; Nur Azizah (Al-Munawwarah : Jurnal Pendidikan Islam, 2025)
The development of learning, which is still dominated by conventional methods, has resulted in low student interest and focus in Islamic Religious Education (ISE). This situation demands innovations in more interactive and student-centered learning, one of which is the Problem-Based Learning (PBL) model, which emphasizes problem-solving as the core of learning. This research employed a descriptive qualitative approach at SMKN 1 Tambang, with Islamic Religious Education (ISE) teachers, the principal, and students as subjects. Data collection techniques were conducted through observation, interviews, and documentation. Data were then analyzed using an interactive analysis model through data reduction, data presentation, and conclusion drawing, with validity tested through triangulation of sources and methods. The results of the study indicate that: the implementation of the PBL model in ISE learning has been quite successful through the stages of problem-posing, discussion, and presentation, thus increasing student engagement. The application of PBL has been able to increase student interest in learning, as indicated by increased enthusiasm and engagement in learning. The PBL model also improves student focus because they are directly involved in the learning process. Challenges encountered include time constraints, differences in student readiness, and a lack of student engagement in understanding the problems. Overall, the Problem-Based Learning (PBL) model is effective in increasing student interest and focus in learning, although it still requires optimal management for optimal implementation.